A SURVEY-BASED STUDY OF PROJECT MANAGEMENT PROBLEMS IN SMALL AND MEDIUM SCALE ENTERPRISES (SMEs) IN NIGERIA - U.C., Ihesiene (European Scientific Journal, ESJ, 2014)
Project management has been mostly researched and applied within the context of large scale businesses in both private and public sectors of the Nigerian economy. Given the need for national transformation and sustainable development through revitalization of the SME sub-sector, the study of management of projects in SMEs has become imperative. Empirical evidences show lack of articulated framework for management of small projects and explain the estimated 80% failure rates for SMEs within five years of start-up. This paper aims at a survey-based investigation of project management problems in Warri and by extension their impact on national development as well as recommending deliberate steps vital for efficient project delivery in SMEs such as: application of PM methods within acceptable economic and political frameworks, establishment of project management offices (PMOs) in SMEs as statutory requirement, incentives such as subsidizing cost of software and removal of multiple levies, dealing with over-bearing owner-managers that challenge project management process, establishment of project monitoring and evaluation units at local government level, engagement of PM professionals in projects among other steps. The results indicate that Management Problem is the greatest problem of management of projects within SME context. The foregoing will be helpful and of interest to students, researchers, policy makers and other stakeholders of sustainable development. SME stakeholders should make deliberate and urgent efforts at adopting project management for effective project delivery regardless of size and form.